Sonoelastography and Lumbopelvic Muscle Stiffness in Patients with Low Back Pain: A Systematic Review: Sonoelastography and Lumbopelvic Muscle Stiffness in LBP - Rafsanjani Deh Qazi, Hossein; Mohseni Bandpei, Mohammad Ali; Rahmani, Nahid (Galen Medical Journal, 2023)
This study aimed to systematically review studies conducted on the application of sonoelastography (SE) to evaluate lumbopelvic muscle stiffness in patients with low back pain (LBP). All relevant articles were retrieved from the available electronic databases, including PubMed, Web of Science, Scopus, EMBASE, Cochrane library, and CINAHL, using the keywords â€œSonoelastographyâ€, â€œElasticity Imaging Techniqueâ€, â€œMuscle Stiffnessâ€, â€œModulus Elasticityâ€, â€œLow Back Painâ€. After initial searches, studies that met the inclusion criteria (i.e., published in English and sonoelastography were used to assess lumbopelvic muscle stiffness in both patients with LBP and healthy individuals) were enrolled. Also, any animal research, abstract of the seminar and/or conference, and/or non-English-language article were excluded. The quality of the studies was assessed using the Physiotherapy Evidence Database (PEDro) scale. In total, eight relevant studies were selected for review. Three studies were considered to have excellent quality, and five were considered fair quality using the PEDro scale. All reviewed studies have reported that SE can be considered a non-invasive method for quantifying changes in lumbopelvic muscle stiffness. Muscle stiffness was significantly higher in LBP patients compared to healthy persons, as well as across subgroups of LBP patients in various test postures (PË‚0.05). Only one study was conducted on the reliability of SE in healthy individuals, while another examined the validity of SE imaging. The results of the present systematic review indicated that SE imaging is a reliable and valid tool to identify muscle changes that occur in patients with LBP and evaluate the effects of rehabilitation treatment.